EFL Students’ Difficulties with Lexical and Syntactic Features of News Headlines and News Stories - Al-Jarf, Reima (Technium Social Sciences Journal, 2021)
Sixty-eight undergraduate translation students received direct instruction in the features of news headlines and news stories. A week later, they took a test that required them to identify the syntactic and lexical features of a sample of news headlines and news stories, supply deleted word, and substitute punctuation marks, infinitives, and block language by their meanings. Results showed that 75% of the subjects could identify initials, 72% recognized surnames and infinitives used instead of the ‘future’, 51% recognized deleted articles, 49% identified block language, 21% identified passive without agent, 19% recognized instances were verb “to be” was deleted, and 6% identified ellipted words. Incorrect responses revealed syntactic and semantic/lexical problems, lack of knowledge of current world events, and insufficient ability to apply features of newspaper language to news headlines and news stories unseen before. To help students read and comprehend news headlines and news stories, pedagogical implications are given.